Efficacy and hypoglycemic risk of sitagliptin in obese/overweight patients with type 2 diabetes compared with GLP-1 receptor agonists: A meta-analysis. Issue 36 (September 2019) - Dai, Danping; Mao, Yiyang; Jin, Haiying; Zhang, Wei
Abstract: Objective: The purpose of this study was to assess the efficacy and hypoglycemic risk of sitagliptin versus that of GLP-1 receptor agonists in the management of obese/overweight patients with T2DM. Methods: EMBASE, PubMed, Cochrane Library, and ClinicalTrials.gov were searched; randomized controlled trials comparing the efficacy of sitagliptin versus that of GLP-1 receptor agonists in obese/overweight patients with T2DM were included. The mean BMI of participants for each study was ≥30 kg/m 2 . We conducted a meta-analysis according to the methods specified in the Cochrane Handbook for Systematic Reviews of Interventions. RevMan 5.1 software was used to perform the meta-analysis. The Cochrane Q test and I 2 statistics were used to estimate the heterogeneity among studies. The results are expressed as the mean difference (MD) or risk ratio (RR) with 95% confidence intervals. Results: A total of 8 eligible studies were included in our meta-analysis. Compared with GLP-1 receptor agonists, sitagliptin was less effective at reducing HbA1c (0.42 [0.27, 0.56]), FPG (0.78 [0.36, 1.19]), PPG (2.61 [1.35, 3.87]), and body weight (1.42 [0.71, 2.14]). Conversely, there were no significant differences in SBP reduction (0.38 [−1.14, 1.89]), DBP reduction (−0.30 [−1.00, 0.39]), and hypoglycemic risk (1.09 [0.50, 2.35]). Conclusion: For obese/overweight patients, sitagliptin may exert a less potent effect on HbA1C, FPG, PPG, and weight reduction than GLP-1 receptor agonists, but these drugs had a similar efficacy in reducing blood pressure; furthermore, there was no significant difference in hypoglycemic risk. Abstract : Supplemental Digital Content is available in the text